2017
DOI: 10.1021/acs.joc.7b00687
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Transfer (HAT) Processes Promoted by the Quinolinimide-N-oxyl Radical. A Kinetic and Theoretical Study

Abstract: A kinetic study of the hydrogen atom transfer (HAT) reactions from a series of organic compounds to the quinolinimide-N-oxyl radical (QINO) was performed in CH 3 CN. The HAT rate constants are significantly higher than those observed with the phthalimide-N-oxyl radical (PINO) as a result of enthalpic and polar effects due to the presence of the Nheteroaromatic ring in QINO. The relevance of polar effects is supported by theoretical calculations conducted for the reactions of the two N-oxyl radicals with toluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 63 publications
3
30
0
1
Order By: Relevance
“…OH discussed above . Along a similar line, the up to 20‐fold increase in the k H value for HAT from the benzylic C−H bonds of alkylaromatic substrates to the quinolinimide‐ N ‐oxyl radical (QINO) measured on going from acetonitrile to acetonitrile containing 0.15 m HClO 4 was explained accordingly in terms of QINO activation through protonation of the heteroaromatic nitrogen atom …”
Section: C−h Bond Deactivationmentioning
confidence: 52%
See 2 more Smart Citations
“…OH discussed above . Along a similar line, the up to 20‐fold increase in the k H value for HAT from the benzylic C−H bonds of alkylaromatic substrates to the quinolinimide‐ N ‐oxyl radical (QINO) measured on going from acetonitrile to acetonitrile containing 0.15 m HClO 4 was explained accordingly in terms of QINO activation through protonation of the heteroaromatic nitrogen atom …”
Section: C−h Bond Deactivationmentioning
confidence: 52%
“…[59] This behavior can be rationalized on the basis of an activation of the PINO radical toward HATb yp rotonation, in line with the effect of HBD solvents on HATf rom C À H bonds of aliphatic hydrocarbons to CumOC and COH discussed above. [61] When the reactions of PINO with tertiary amides were investigated, decreases in the k H values by greater than two orders of magnitude were measured in acetonitrile following addition of 0.1m HClO 4 . [61] When the reactions of PINO with tertiary amides were investigated, decreases in the k H values by greater than two orders of magnitude were measured in acetonitrile following addition of 0.1m HClO 4 .…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, it has been demonstrated that PhI(OAc) 2 was able to initiate the generation of PINO radical from NHPI [30,31]. It is also known that the PINO radical was easy to abstract a hydrogen atom from a benzylic position of the organic substrate [39,40,41]. We designed one radical scavenging experiment (Figure 5a) to validate that the PINO radical was indeed formed in our reaction system.…”
Section: Resultsmentioning
confidence: 83%
“…OH übereinstimmt . Ähnlich wurde auch die bis zu 20‐fache Zunahme von k H für den HAT aus den benzylischen C‐H‐Bindungen von Alkylaromaten auf das Chinolinimid‐ N ‐oxyl‐Radikal (QINO) beim Übergang von Acetonitril zu Acetonitril mit 0.15 m HClO 4 mit der QINO‐Aktivierung über die Protonierung des heteroaromatischen Stickstoffatoms begründet …”
Section: C‐h‐bindungsdeaktivierungunclassified